Synthesis and structure of 6-bromo-2-(diethoxymethyl)-2-hydroxy-3-phenyl-2,3-dihydro-1H-imidazo[1,2-a]pyridin-4-ium chloride acetonitrile monosolvate - Firudin I. Guseinov; Aida I. Samigullina; Tuncer Hökelek; Sahil Z. Hamidov; Jamal Lasri; Khudayar I. Hasanov; Tahir A. Javadzade; Alebel N. Belay (Acta Crystallographica Section E: Crystallographic Communications)
In the title solvated molecular salt, C18H22BrN2O3+·Cl−·CH3CN, the imidazole ring is in envelope conformation and the pyridine and phenyl rings are oriented at a dihedral angle of 72.52 (5)°. In the crystal, O—H...Cl and N—H...Cl hydrogen bonds link the cations and anions into centrosymmetric tetramers enclosing R24(12) loops. Short Br...Cl [3.2313 (4) Å] and O...Cl [3.0490 (10) Å] contacts are observed. A Hirshfeld surface analysis of the structure indicates that the most important contributions for the crystal packing are from H...H (52.4%), H...C/C...H (12.1%), H...Br/Br...H (11.0%) and H...Cl/Cl...H (10.2%) interactions.